Enhancement of Buckling Resistance of Aluminized Long Columns of Stainless Steel AISI 303 - Ahmed Naïf Al-Khazraji (Al-Khwarizmi College of Engineering – University of Baghdad, 2016)
This paper has investigated experimentally the dynamic buckling behavior of AISI 303 stainless steel Aluminized and as received long columns. These columns, hot-dip aluminized and as received, are tested under dynamic buckling, 22 specimens, without aluminizing (type 1), and 50 specimens, with hot-dip aluminizing at different aluminizing conditions of dipping temperature and dipping time (type 2), are tested under dynamic compression loading and under dynamic combined loading (compression and bending) by using a rotating buckling test machine. The experimental results are compared with Perry Robertson interaction formula that used for long columns. Greenhill formula is used to get a mathematical model that descripts the buckling behavior of the specimens of type (1) under dynamic compression loading. The experimental results obtained show an advantageous influence of hot-dip aluminizing treatment on dynamic buckling behavior of AISI 303 stainless steel long columns. The improvement based on the average value of critical buckling stress, are as follow: (64.8 %) for long columns type (2), compared with columns type (1), under dynamic compression loading, and (56.6 %) for long columns type (2), compared with columns type (1), under dynamic combined loading, and (33.3 %) for long columns type (2) compared with Perry Robertson critical buckling stress.